DERIVATIVE ULTRA-VIOLET SPECTROSCOPIC METHOD FOR THE ESTIMATION OF CERBERIN IN RAT PLASMA - PRASANTH SS,; RAJASEKARAN A, (International Journal of Pharma and Bio Sciences, 2015)
Cerberin (2-o-Acetyl neriifolin) is the principal cardiac glycoside present in seeds of Cerbera odollam.The seeds of Cerbera odollam are used as a poison for suicidal as well as homicidal purpose by people around the world. Its detection in body fluids is somewhat difficult .The present study aims to develop a simple Ultra Violet derivative spectroscopic method for the estimation of cerberin from rat plasma without previous chemical separation using fourth derivative of the zero-order absorption spectra and the integrated area of the peak (valley) ranging from wavelength 305.2 to 307.2 nm.